Financial Performance and Value Analysis Company and Influence to Stock Price - Pita Sari (PT. Hanken SUkses Jaya, 2021)
The purpose of this study is to determine whether financial Performance and firm value affect the stock price of banking and whether financial Performance and substantial value simultaneously affect the stock price of banking. Return measures financial Performance on Assets (ROA). Firm value is calculated by Price to Book Value (PBV). The population in this study were banks listed on the IDX in 2017-2019, which amounted to 43 banks. The research sample was taken based on a purposive sampling technique with a total model of 13 banks. The method of analysis in this study using the Multiple Linear Regression Test is used to test whether Return on Assets (ROA) and Price to Book Value (PBV) affect stock prices. The F test is used to test whether Return on Assets (ROA) and Price to Book Value (PBV) together affect banking stock prices. Based on the results of this study, it is known that the Return on Assets (ROA) is 0.316, which means that it does not affect banking stock prices because it is >0.05. Meanwhile, the Price to Book Value (PBV) is 0.000, which affects the banking stock price because it is <0.005. The results of the F test show that the sig value is 0.00, which means that Return on Assets (ROA) and Price to Book Value (PBV) together affect banking stock prices because <0.05.